Biodiversity and the art of living. Food as an aesthetic and environmental experience (Itinera, 2025)
This essay explores the relationship between biodiversity and the art of living through the lens of food, understood as both an aesthetic and environmental experience. It begins by examining the current biodiversity crisis and the proliferation of industrial food systems, which contribute to unsustainable and unhealthy lifestyles. The aesthetic dimension of eating is then analyzed in light of “aesthetic capitalism” (Böhme) and the greenwashing practices it often entails. Within the theoretical framework of Everyday Aesthetics (Berleant, Saito), the essay proposes an alternative food culture and experience grounded in the concepts of engagement and care. Drawing on the Greek notion of diaita — understood not simply as a dietary regimen but as a harmonious and mindful way of life —the essay reinterprets gastronomic experience as an embodied and situated aesthetic practice, capable of integrating sensoriality, ethics, and sustainability. In this sense, nourishment is no longer reduced to a consumable object but is redefined as a form of aisthesis: a mode of sensitive knowledge that respects and fosters both natural and cultural biodiversity.
Keywords: biodiversity; everyday aesthetics; environmental aesthetics; food aesthetics